2005
DOI: 10.1111/j.1365-294x.2005.02485.x
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite variation and structure of 28 populations of the common wetland plant, Lychnis flos‐cuculi L., in a fragmented landscape

Abstract: Habitat fragmentation is known to cause genetic differentiation between small populations of rare species and decrease genetic variation within such populations. However, common species with recently fragmented populations have rarely been studied in this context. We investigated genetic variation and its relationship to population size and geographical isolation of populations of the common plant species, Lychnis flos-cuculi L., in fragmented fen grasslands. We analysed 467 plants from 28 L. flos-cuculi popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
51
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 65 publications
5
51
2
Order By: Relevance
“…Many studies have reported significant relationships between population size and genetic variation (for example, Young et al, 1999;Galeuchet et al, 2005;Gao, 2005;Leim et al, 2006). However, a previous study on M. stellata published by Nakashima and Sakai (2003) did not detect such a relationship, possibly because the measure of population size they used was not the number of reproductive individuals but the number of individuals within populations.…”
Section: Factors Influencing the Level Of Within-population Genetic Vmentioning
confidence: 51%
See 3 more Smart Citations
“…Many studies have reported significant relationships between population size and genetic variation (for example, Young et al, 1999;Galeuchet et al, 2005;Gao, 2005;Leim et al, 2006). However, a previous study on M. stellata published by Nakashima and Sakai (2003) did not detect such a relationship, possibly because the measure of population size they used was not the number of reproductive individuals but the number of individuals within populations.…”
Section: Factors Influencing the Level Of Within-population Genetic Vmentioning
confidence: 51%
“…Since it is more difficult to measure the Genetic variation in Magnolia stellata populations I Tamaki et al degree of population isolation than population size, good measures for quantifying the degree of population isolation have not yet been established. However, we detected significant relationships between the degree of population isolation and genetic variation, using the number of surrounding populations as the measure of isolation, whereas the distance from the nearest population was used in many previous studies (for example, Llorens et al, 2004;Galeuchet et al, 2005;Lu et al, 2005). Thus, the detection of a significant relationship in this study, and the failure of many of the cited studies to detect such relationship, supports the assertion by Moilanen and Nieminen (2002) that the number of surrounding populations is a much better indicator of isolation than the distance from the nearest population.…”
Section: Factors Influencing the Level Of Within-population Genetic Vmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, there are inherent difficulties in detecting genetic consequences of recent habitat fragmentation on natural populations due to complex reasons such as the influence of historical population structure (Avise et al, 1987;Cunningham & Moritz, 1998) or the dispersal characteristics of species itself (Keyghobadi et al, 2005). Some scientists claimed that human-induced habitat fragmentation might be too recent to detect pronounced genetic effects in some situations, especially for high gene flow species (Sumner et al, 2004;Galeuchet et al, 2005). On the other hand, given the appropriate control populations, some scientists still have identified the effect of recent habitat fragmentation in terms of decreased genetic diversity and increased differentiation (Williams et al, 2003;Keller & Largiader, 2003).…”
Section: Population Genetic Structurementioning
confidence: 99%